ANALISIS PENGAMBILAN KEPUTUSAN PEMBELIAN KARKAS BURUNG PUYUH (Coturnix coturnix) TERHADAP PERILAKU KONSUMEN DI KABUPATEN SUKABUMI (Suatu Kasus pada Konsumen CV. Slamet Quail Farm di Kecamatan Cikembar Kabupaten Sukabumi) - Siti Maryam; Dety Sukmawati; Euis Dasipah; Tuti Gantini; Maman Haeruman (Universitas Galuh, 2023)
In this study to analyze the consumer behavior of quail carcass towards the decision making of purchasing quail carcass, in the Sukabumi Regency. For research areas carried out using a purposive sampling system, namely in CV. Slamet Quail Farm (SQF) in Cikembar District, Sukabumi Regency. Sampling using nonprobability sampling method with accidental sampling technique. The number of samples is 90, with the conditions that the respondents are willing to be interviewed in accordance with the guidelines. Analysis was carried out descriptively, to analyze the relationship between behavior on consumer decisions using Fishbein multi-attribute analysis and also Spearman's Rank correlation. The results of the study show that the characteristics of consumers buying quail carcasses in Sukabumi Regency are dominated by women aged between 31-40 years, working as private employees, income levels between Rp. 2,000,000 - Rp. 3,000,000 per month and having 2 family members borne. Remote outlet locations are the main obstacle informed by consumers in buying quail carcasses. The attributes of the benefits of purchasing quail carcasses with the highest number of values were obtained at the level of importance and trust in the results of the fishbein mutriattribute. The behavioral value (Ao) of purchasing quail carcass is positive, despite the many benefits and nutritional content in quail carcass.